-1/2 + (3/4 * 4/9) Here we need to start by finding the common denominator for 3/4 and 4/9.

For this problem, you can just multiply the numerators: (3*4)=12

And the denominators: (4*9)=36

So we get the fraction 12/36.

To simplify this equation we will reduce the fraction by dividing by 4. We then get 3/9

Now we have -1/2 + 3/9

To get a common denominator we will cross multiply:

-1*9= -9

2*3=6

2*9 and 9*2 = 18 and 18 so we get:

-9/18+6/18

Now we can add the numerators and the denominator remains the same and we get the answer: -3/18

Hope this helps!